2020
DOI: 10.1093/cercor/bhaa086
|View full text |Cite
|
Sign up to set email alerts
|

Different Principles Govern Different Scales of Brain Folding

Abstract: The signature folds of the human brain are formed through a complex and developmentally regulated process. In vitro and in silico models of this process demonstrate a random pattern of sulci and gyri, unlike the highly ordered and conserved structure seen in the human cortex. Here, we account for the large-scale pattern of cortical folding by combining advanced fetal magnetic resonance imaging with nonlinear diffeomorphic registration and volumetric analysis. Our analysis demonstrates that in utero brain growt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Bush et al previously suggested that the Sylvian fissure appears by convergence of the anterior and posterior poles of the embryonic telencephalon and proposed a convergence index for the adult brain, calculated as the Euclidean distance/transcortical distance ratio, that returns its highest values around the fissure [20]. Recently, Mallela et al showed that, contrary to intralobar sulci, the subarachnoid space in the Sylvian fissure contracts as the fissure grows; the edges of this singular fold do not bend, they converge [21]. Here, we show that the distance between the frontal and temporal lobes diminishes with gestational time as does the volume of the Sylvian fissure as a result of represents the volumetric growth of the frontal lobe, central core, temporal and parietal lobes respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bush et al previously suggested that the Sylvian fissure appears by convergence of the anterior and posterior poles of the embryonic telencephalon and proposed a convergence index for the adult brain, calculated as the Euclidean distance/transcortical distance ratio, that returns its highest values around the fissure [20]. Recently, Mallela et al showed that, contrary to intralobar sulci, the subarachnoid space in the Sylvian fissure contracts as the fissure grows; the edges of this singular fold do not bend, they converge [21]. Here, we show that the distance between the frontal and temporal lobes diminishes with gestational time as does the volume of the Sylvian fissure as a result of represents the volumetric growth of the frontal lobe, central core, temporal and parietal lobes respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Symmetric Normalization (SyN) algorithm in the Advanced Normalization Tools (ANTs) package, that registers weekly image pairs (Week 24 to 25, etc.) was used to quantify week-to-week changes as described by Mallela et al [21] The original segmentations in the Gholipour atlas [22] was used as the ground truth to validate the accuracy of our registration.…”
Section: Anatomical Dissectionsmentioning
confidence: 99%
“…The insula is also the focal point around which the Sylvian fissure, and accordingly the operculae of the frontal, parietal, and temporal lobes, are arranged. [18][19][20] Here we show that the distinct C-shape of the cerebrum is a function of these operculae closing over the insula during fetal development. Accordingly, understanding the determinants of how the other lobes overgrow the insula to close to Sylvian fissure is paramount to understanding the global configuration of cerebrum.…”
Section: Introductionmentioning
confidence: 56%
“…Since 13 gw, cells from the subpallial neurons migrate into the insular cortex along the radial glial fascicle reaching the final configuration before birth ( 16 ). Mallela et al ( 17 , 18 ) found different gene expressions from the opercula to the insula resulting in the highest proliferation of the former allowing their growth over the insula. This different origin might explain the fact that the tracts that developed later connecting frontal, temporal, and parietooccipital regions ‘avoid crossing the insula', thus being located ventral or dorsal to it, and in some cases wrapping around it with specific curved patterns ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 13 gw, cells from the subpallial neurons migrate into the insular cortex along the radial glial fascicle reaching the final configuration before birth (16). Mallela et al (17,18) found different gene expressions from the opercula to the insula resulting in the highest proliferation of the former allowing their growth over the insula. This different origin might explain the fact that the tracts that developed later FIGURE 8 | An 18-year-old left-handed girl presented with medically refractory epilepsy that was symptomatic since the age of 3 years due to a perinatal stroke in the territory of the left middle cerebral artery.…”
Section: Figure 5 | (A)mentioning
confidence: 99%